A study on laparoscopic sterilisation using 5mm laparoscope and direct trocar entry method - C., Mohammed sidhiq; H., Mini C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparoscopic sterilization is a widely accepted method of permanent contraception. The techniques of abdominal entry are open direct trocar and veress method. The objectives of this study were to performance and practice of 5mm direct trocar entry techniques in Laparoscopic sterilization. To prepare a list of benefits and complications. Methods: Retrospective analysis of patients who underwent direct 5mm trocar entry for laparoscopic sterilization. Period: 1st April 2017 to 30th November 2017. Patient came on the day of surgery with empty stomach. Intravenous pethedine 50mg and phenergan 12.5mg and antibiotics were given. Injection lignocaine intraumbilically and incision of 5mm was made. 5mm trocar and canula inserted directly. 5mm scope inserted. After ensuring peritoneal cavity, pneumoperitonium created. Secondary 7mm port made under vision and ring applicator inserted and fallop ring applied on both tubes. Port closure done by N Butyl 2 cyano accrylate. Patient was observed for 6 hours and discharged with analgesics and antibiotics. Results: We operated 220 interval sterilizations and 31 posts MTP. In 250 cases, the method was successful. Only in one woman 5mm trocar was insufficient to make peritoneal entry since the patient was morbidly obese. Hence 10mm trocar was used. Conclusions: Laparoscopic tubal sterilization can be done with 5mm laparoscope and direct trocar entry method is safe and saves time.